(untitled) (Research, Society and Development, 2022)
Objective: To report on the experiences of organising the remote online event “I Encuentro Internacional de Agentes Mayores: Voces de la Experiência”. Method: experience report on a remote event held in the second half of 2021. It involved elderly people from health institutions in six Latin American countries. Organizers: Research Groups: Social Nursing and Adult Care (GIESCA) of the Santo Toribio de Mogrovejo Catholic University of the city of Chiclayo-Peru and Management of Professional Training and Qualification: Education and Health (GESPRO) of the Fluminense Federal University of the city of Niterói -Brazil. Results and discussion: the organization of the remote event took place through online meetings with the leaders of the Peru/Brazil research groups and the advice of GESPRO. Active and healthy aging was verified through: raising awareness, social inclusion and strengthening dialogue among the elderly. There was active participation of the elderly. The integration between program managers, research groups and representatives of Latin American countries made it possible to give voice to this population through the use of digital technology. Conclusion: The experience report on the organization of that event made it possible reveal the current state of health care for the elderly, through the exploration of the remote world for social inclusion. It provided the visibility and appreciation of the cultural background and experiences of the elderly. The well-being of participants and guests was fostered through dialogue, strengthening and favoring active and healthy aging, reducing distances and continuing human interactions.